(untitled) (Applied Biological Research, 2017)
The present research was aimed to screen and characterize limonin degrading microorganisms and assess their efficiency in limonin reduction. ight bacterial isolates from kinnow orchard soil and two yeast isolates from soft kinnow peel and kinnow waste site (Abohar, Punjab) were isolated. All the isolates were evaluated for their limonin utilizing ability by swarm plate assay. Two bacterial isolates (S1 and S2) and both yeast isolates (PY1 and AY1) showed considerable zone of TTC reduction. All the four selected isolates were studied for their growth profile and rate of limonin degradation in minimal media broth with limonin (28 ppm) as a sole carbon source. Bacterial isolate S1 showed maximum limonin degradation (52.9%), followed by yeast isolates PY1 (48.5%), AY1 (31.1%) and bacterial isolate S2 (26.4%). Ca-alginate immobilized cells of PY1 yeast and S1 bacteria were also studied for their limonin degrading ability which respectively showed 94.8 and 98% limonin reduction. The two microbial isolates were molecularly identified as Bacillus megaterium strain KU570370.1. on 16SrDNA basis and Meyerozyma caribbica isolate KP860076.1. on 18S rDNA basis These microbial isolates could be exploited for the production of enzyme limonin dehydrogenase for possible use in debittering kinnow juice.